CLINICAL EFFICACY OF A BETABLOCKERS THERAPY IN PATIENTS WITH CHRONIC HEART FAILURE ON THE BACKGROUND OF POSTINFARCTION CARDIOSCLEROSIS - Ol'ga Osipova; Vladimir Kulikovskii; Kseniya Plaksina; Evgenii Shabanov; Elena Gosteva (Belgorod National Research University, 2017)
Despite the fact that betablockers (BBs) are one of the main groups of therapy of patients with acute myocardial infarction (AMI), the comparative effectiveness of various BBs in patients with postinfarction cardiosclerosis (PICS) is uncertain. There was performed comparative analysis of clinical efficacy of BBs in patients with chronic heart failure (CHF) on the background of coronary heart disease (CHD), PICS. There was evaluated the impact of metoprolol succinate, carvedilol, bisoprolol and betaxolol on blood pressure (BP), left ventricular ejection fraction (LVEF), change the functional class of chronic heart failure, and mortality in patients over 4 years. It is established that the BBs therapyblood pressure decreased equally, without significant differences between the groups (р˃0,05). There was a positive effect on the increase of the LVEF all the BBs (p